Upaya Meningkatkan Critical Thinking Skills Peserta Didik Kelas XI-IPA 3 SMAN 2 Sampang Melalui Model Problem Based Learning (PBL) Pada Materi Barisan - Siti Wasilah (Wacana Didaktika, 2019)
The objectives of this study are: 1) to describe the critical thinking skills of students in class XI-IPA 3 SMAN 2 Sampang through the Problem Based Learning (PBL) model on the row material. 2) describe the completeness of student learning outcomes class XI-IPA 3 SMAN 2 Sampang through the Problem Based Learning (PBL) model on the row material. This research uses Classroom Action Research (CAR) with 2 cycles. Data collection and analysis techniques used the method of observation of students' activities and formative test methods. The results of the analysis of the data obtained are as follows: (1) Critical Thinking Skills of students in each cycle there is an increase, which is marked by increased student activity in cycle I by 1.3 (less active) increased in cycle II to 1.8 (enough active). (2) The percentage of mastery learning in cycle I was 63.64%, increasing in cycle II to 86.36%. Based on the results of data analysis, it can be concluded that the application of Problem Based Learning (PBL) can improve the Critical Thinking Skills of class XI-IPA 3 students in Sampang on row material. Keywords: Critical Thinking Skills, Higher Order Thinking Skills (HOTS), Problem Based Learning (PBL) Abstrak: Tujuan penelitian ini adalah: 1) mendeskripsikan critical thinking skills peserta didik kelas XI-IPA 3 SMAN 2 sampang melalui model Problem Based Learning (PBL) pada materi barisan. 2) mendeskripsikan ketuntasan hasil belajar peserta didik kelas XI-IPA 3 SMAN 2 Sampang melalui model Problem Based Learning (PBL) pada materi barisan. Penelitian ini menggunakan Penelitian Tindakan Kelas (PTK) dengan 2 siklus. Teknik pengumpulan dan analisis data menggunakan metode observasi aktivitas peserta didik dan metode tes formatif. Hasil analisis data yang diperoleh sebagai berikut: (1) Critical Thinking Skills peserta didik pada tiap siklus terjadi peningkatan, yaitu dengan ditandai meningkatnya keaktifan peserta didik pada siklus I sebesar 1,3 (kurang aktif) meningkat pada siklus II menjadi 1,8 (cukup aktif). (2) Persentase ketuntasan belajar pada siklus I sebesar 63,64% meningkat pada siklus II menjadi 86,36%. Berdasarkan hasil analisis data, dapat disimpulkan bahwa penerapan Problem Based Learning (PBL) dapat meningkatkan Critical Thinking Skills peserta didik kelas XI-IPA 3 SMAN 2 sampang pada materi barisan